2018
DOI: 10.1186/s12885-018-4208-x
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib treatment after platinum-based therapy in elderly patients with non-small-cell lung cancer in routine clinical practice – results from the ElderTac study

Abstract: BackgroundIn this prospective non-interventional study, the effectiveness and tolerability of erlotinib in elderly patients with non-small-cell lung cancer (NSCLC) after ≥1 platinum-based chemotherapy were assessed.MethodsA total of 385 patients ≥65 years of age with advanced NSCLC receiving erlotinib were observed over 12 months. The primary endpoint was the 1-year overall survival (OS) rate.ResultsPatients were predominantly Caucasian (99.2%), a mean of 73 years old; 24.7% had an Eastern Cooperative Oncology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Median age at diagnosis of all patients was 66 years (range, 18–94 years). Using median age and previous clinical studies as guides (Brueckl et al, 2018; Feliciano et al, 2018; Hutchins et al, 1999; Lembicz et al, 2018; Lewis et al, 2003), we divided the included patients into two groups based on age: younger (aged <65 years) ( N = 729), and older (aged ≥65 years) ( N = 890) patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median age at diagnosis of all patients was 66 years (range, 18–94 years). Using median age and previous clinical studies as guides (Brueckl et al, 2018; Feliciano et al, 2018; Hutchins et al, 1999; Lembicz et al, 2018; Lewis et al, 2003), we divided the included patients into two groups based on age: younger (aged <65 years) ( N = 729), and older (aged ≥65 years) ( N = 890) patients.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of pulmonary LCNEC is rare, representing only 3% of all types of diagnosed lung cancer. Thus, the published studies of pulmonary LCNEC commonly included limited patients (Brueckl et al, 2018; Carretta et al, 2000; Mazieres et al, 2002; Zacharias et al, 2003). In this study, we found that more LCNEC patients were white, married, of stage I, with tumor size <5 cm in the older group; and the proportion of patients undergoing surgery, radiotherapy, and chemotherapy were significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…non-small cell lung cancer (nSclc) is a lung malignancy that seriously threatens human health, and its poor prognosis largely results from cancer cell survival and metastasis (1)(2)(3). The methods of radiotherapy and chemotherapy used to treat nSclc have improved; however, the 5-year survival of patients with nSclc remains poor (4)(5)(6)(7). Therefore, strategies that suppress cancer cell survival and metastasis are required for the treatment of nSclc.…”
Section: Introductionmentioning
confidence: 99%
“…Although these series included patients ranging from 24 to 88 years old, the elderly were underrepresented and specific data regarding octogenarians are limited. Previous studies have reported on the safety and efficacy of TKIs in elderly patients, as shown by osimertinib treatment for T790M-positive NSCLC [36] or erlotinib treatment for NSCLC after one or more platinum-based chemotherapy regimens [37]. However, the definition of “elderly” is highly heterogeneous among these studies, including patients ranging from 65 [37] to 75 years old [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on the safety and efficacy of TKIs in elderly patients, as shown by osimertinib treatment for T790M-positive NSCLC [36] or erlotinib treatment for NSCLC after one or more platinum-based chemotherapy regimens [37]. However, the definition of “elderly” is highly heterogeneous among these studies, including patients ranging from 65 [37] to 75 years old [36]. Recently, a multicenter real-world study (OCTOMUT) evaluated the tolerability and efficacy of TKIs in Caucasian octogenarian patients with EGFR -mutated NSCLC [38].…”
Section: Discussionmentioning
confidence: 99%